THE CONTRIBUTION OF ARTIFICIAL INTELLIGENCE IN ENHANCING THE SUCCESS AND SUSTAINABILITY OF STARTUPS – PRACTICAL MODELS - Wail Meliani; Hichem Basti (International Journal of Innovative Technologies in Social Science, 2024)
This study aims to explore the contribution of artificial intelligence (AI) in enhancing the success and sustainability of startups by presenting practical models of companies from different continents that have adopted innovative AI-driven solutions. The research focuses on the role of these technologies in fostering innovation, supporting decision-making, improving performance, and identifying opportunities that strengthen competitiveness. The descriptive-analytical method was applied to present the conceptual frameworks related to the variables, while the case study method was adopted to analyze the experiences of six startups from various sectors and continents: Cropin from India (Asia) in smart agriculture, Resistant AI from the Czech Republic (Europe) in financial system protection, Mistral AI from France (Europe) in language model development, NotCo from Chile (America) in plant-based food innovation, Amini AI from Kenya (Africa) in environmental data collection, and Harrison AI from Australia (Oceania) in medical diagnostics. The findings reveal that the adoption of AI enabled these startups to automate processes, efficiently analyze data, enhance customer experience, and adapt to dynamic markets, which provided them with an exceptional ability to achieve early success and strengthen their prospects for sustainability despite their relatively recent establishment.